2016
DOI: 10.15581/003.29.2.63-79
|View full text |Cite
|
Sign up to set email alerts
|

Reference press metamorphosis in the digital context: clickbait and tabloid strategies in Elpais.com

Abstract: In a context marked by technological uncertainty and the search for a viable business model, the digital media have succumbed to various strategies to attract audience, reflected in the clicks generated by each reader. This article focuses attention on a reference newspaper as El País, to discuss what options were incorporated in order to attract visitors to the website. By using a quantitative and qualitative methodology, a study was carried out on four sections added by Elpais.com in the last two years: SMod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
0
16
0
3
Order By: Relevance
“…The support of Hypothesis 1, which states that understanding hard news journalistic standards is associated with increased headline literacy, suggests future avenues for both education efforts and research. As discussed, headlines can often be misleading (Palau-Sampio, 2016). Advocates for NL argue the need to continually grow and expand NL programs, both in terms of content and of incorporation into education (Beyerstein, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The support of Hypothesis 1, which states that understanding hard news journalistic standards is associated with increased headline literacy, suggests future avenues for both education efforts and research. As discussed, headlines can often be misleading (Palau-Sampio, 2016). Advocates for NL argue the need to continually grow and expand NL programs, both in terms of content and of incorporation into education (Beyerstein, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found clickbait strategies appearing in headlines from conventional news sources. Palau-Sampio (2016) showed that editors at a prestigious national news organization broke their own style guidelines for headlines by using tabloid-style punctuation tactics including question marks, ellipses, and exclamation marks. In terms of word choice, headlines included wording that intensified emotions, "headline hooks" designed to pique curiosity, and other types of creative wordplay (Palau-Sampio, 2016).…”
Section: Incidental News Exposure In the Digital Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Este dato confirma las tesis de la "trompeta de la desinformación" y del "efecto cascada" mencionados en el marco teórico, pues la mayoría de los mensajes dudosos llegaron a los usuarios a través de los medios de comunicación, que se convierten en el último eslabón de la cadena de transmisión de un número importante de bulos.No obstante, en lo que atañe a nuestro estudio y en aras de una mejor compresión de los datos, hemos segregado los medios de comunicación profesionales de los medios satíricos; y, dentro de los primeros, hemos distinguido entre los medios tradicionales (legacy media) y los medios nativos digitales, en línea con la metodología del Digital News Report, que ha demostrado diferencias a favor de la confianza del público hacia los medios tradicionales en detrimento de los medios online.Efectivamente, al introducir este factor de discriminación, observamos diferencias significativas entre los medios tradicionales, que fueron la fuente de propagación de mensajes dudosos para la audiencia en un 31% de los casos, y los medios online, que lo fueron en el 67% de los casos, más del doble. Ademas, tras el proceso de verificación, el 21% de los mensajes dudosos transmitidos por los medios tradicionales se demostraron falsos, porcentaje que, sin embargo, alcanzó al 50% de los mensajes dudosos transmitidos por los medios online.Estos datos evidencian que, desde el punto de vista científico, no se puede obviar la distinción entre los mensajes dudosos recibidos a través de los llamados "medios de referencia"(Imbert y Vidal-Beneyto, 1986;Labio-Bernal, 2008;Palau-Sampio, 2016), o a través de los medios sensacionalistas y los identificados como "medios de desinformación" especializados en distribuir junk news o noticias basura (Rodríguez-Fernández, 2020). Esta cuestión queda…”
unclassified
“…Taking into account the globalising character of a complex concept as quality, understood as an "expression of different processes for obtaining and managing information, as a result of the application of standards of impartiality and balance, contrast and plurality", in addition to the requirement of variety and originality, research, deepening and independence (Gómez Mompart and Palau-Sampio, 2013: 35), we cannot establish a radical distinction between the informative product and the production circumstances which made it possible. In this sense, some studies have clearly identified the negative effects of certain formulas aimed at increasing profitability of the digital editions of important media, in the context of the search for a business model (O"Donnell and McKnight, 2012;Ramírez de la Piscina et al, 2014;Palau-Sampio, 2016). To these signs of the increasing devaluation of quality we have to add the negative perception of news professionals -a 2014 survey revealed that 81% of Spanish journalists perceive a widespread loss of the capital values of the profession (Gómez, Gutiérrez & Palau, 2015) -and the insufficient trust of readers in the press -the 2012 Eurobarometer revealed, among other international indicators, that only 40% of the EU citizens trust the press (Several authors, 2012).…”
mentioning
confidence: 99%